AFFECT, EMOTION ET SURPRISE DANS LA PERSUASION PUBLICITAIRE. Une revue de la littérature. - Dridi, Monia; Makhlouf, Mouna (British Journal of Marketing Studies, 2014)
A long time, the cognitive approach dominated the consumer research. But with the marketing mutations, an increasing interest was carried to the affect, particularly in the advertising communication. We recognize more and more the role of affect and emotions, such as surprise, in advertising persuasion